2013
DOI: 10.1155/2013/379850
|View full text |Cite
|
Sign up to set email alerts
|

Pinocembrin: A Novel Natural Compound with Versatile Pharmacological and Biological Activities

Abstract: Pinocembrin (5,7-dihydroxyflavanone) is one of the primary flavonoids isolated from the variety of plants, mainly from Pinus heartwood, Eucalyptus, Populus, Euphorbia, and Sparattosperma leucanthum, in the diverse flora and purified by various chromatographic techniques. Pinocembrin is a major flavonoid molecule incorporated as multifunctional in the pharmaceutical industry. Its vast range of pharmacological activities has been well researched including antimicrobial, anti-inflammatory, antioxidant, and antica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
187
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 269 publications
(191 citation statements)
references
References 95 publications
1
187
0
3
Order By: Relevance
“…Tr ( Others compounds present in Buin and Caleu propolis, with antiinflammatory effects were: caffeic acid benzyl ester, caffeic acid prenyl ester (Uwai et al, 2008), ferulic acid, p-coumaric acid (Fernández et al, 1998), apigenin, kaempferol, quercetin-7-methyl-ether (Kim et al, 2004), dicaffeoyl quinic acid (Peluso et al, 1995), caffeic acid cinnamyl ester (Nagaoka et al, 2003), pinocembrin (Rasul et al, 2013;Soromou et al, 2012) and vanillin (Makni et al, 2011).…”
Section: Compounds (Eep)mentioning
confidence: 99%
“…Tr ( Others compounds present in Buin and Caleu propolis, with antiinflammatory effects were: caffeic acid benzyl ester, caffeic acid prenyl ester (Uwai et al, 2008), ferulic acid, p-coumaric acid (Fernández et al, 1998), apigenin, kaempferol, quercetin-7-methyl-ether (Kim et al, 2004), dicaffeoyl quinic acid (Peluso et al, 1995), caffeic acid cinnamyl ester (Nagaoka et al, 2003), pinocembrin (Rasul et al, 2013;Soromou et al, 2012) and vanillin (Makni et al, 2011).…”
Section: Compounds (Eep)mentioning
confidence: 99%
“…It was reported to have multiple actions including anti-platelet aggregant (Jantan et al, 2008), anti-angiogenic activities (Ahn et al, 2009), anti-inflammatory (Soromou et al, 2012), anti-oxidant (Kapoor, 2013;Santos et al, 1998;Yu et al, 2009), and antimicrobial (Paintz and Metzner, 1979). Recently, preclinical studies have suggested pinocembrin protects rat brain against oxidation and apoptosis induced by ischemia-reperfusion both in vivo and in vitro Liu et al, 2008;Rasul et al, 2013;Shi et al, 2011;Soromou et al, 2012;Wang et al, 2013;Wu et al, 2013). Using a permanent focal cerebral ischemia rat model, pinocembrin improved regional cerebral blood flow and reduced the postischemic damage to the neurovascular unit at the dose level of 3, 10, and 30 mg kg À 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Its vast range of pharmacological activities has been well researched including antimicrobial, anti-inflammatory, antioxidant, and anticancer activities. In addition, pinocembrin can be used as neuroprotective against cerebral ischemic injury with a wide therapeutic time window, which may be attributed to its antiexcitotoxic effects (Rasul et al, 2013). Pinostrobin (2) was isolated from Polygonum lapathifolium nodosum quickly penetrates through cytoplasm to the cellular nucleus of the cultured cells, and gives intensive apoptotic response in stimulating leukemic cells in vitro (Smolarz et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…It also improves atherogenic lipid profiles and increases HDL-C levels significantly. These results suggest that compound (3) can be used as an effective antidiabetic cum lipid lowering agent for type 2 diabetes mellitus patients (Singh et al, 2009). β-amyrin acetate (4) isolated from the Alstonia boonei stem bark exhibited profound anti-inflammatory activity (Okoye et al, 2014).…”
Section: Resultsmentioning
confidence: 99%